Neuronal and glial purinergic receptors functions in neuron development and brain disease - del Puerto, Ana; Wandosell, Francisco G.; Garrido, Juan José (Frontiers in Cellular Neuroscience, 2013)
Brain development requires the interaction of complex signalling pathways, involving different cell types and molecules. For a long time, most attention has focused on neurons in a neuronocentric conceptualization of CNS development, these cells fulfilling an intrinsic programme that establishes the brain’s morphology and function. By contrast, glia have mainly been studied as support cells, offering guidance or as the cells that react to brain injury. However, new evidence is appearing that demonstrates a more fundamental role of glial cells in the control of different aspects of neuronal development and function, events in which the influence of neurons is at best weak. Moreover, it is becoming clear that the function and organization of the nervous system depends heavily on reciprocal neuron-glia interactions. During development, neurons are often generated far from their final destination and while intrinsic mechanisms are responsible for neuronal migration and growth, they need support and regulatory influences from glial cells in order to migrate correctly. Similarly, the axons emitted by neurons often have to reach faraway targets and in this sense, glia help define the way that axons grow. Moreover, oligodendrocytes and Schwann cells ultimately envelop axons, contributing to the generation of Nodes of Ranvier. Finally, recent publications show that astrocytes contribute to the modulation of synaptic transmission. In this sense, purinergic receptors are expressed widely by glial cells and neurons, and recent evidence points to multiple roles of purines and purinergic receptors in neuronal development and function, from neurogenesis to axon growth and functional axonal maturation, as well as in pathological conditions in the brain. This review will focus on the role of glial and neuronal secreted purines, and on the purinergic receptors, fundamentally in the control of neuronal development and function, as well as in diseases of the nervous system.